بطاقة الأداء المتوازن كأداة لتقييم الأداء البيئي للمؤسسات دراسة حالة مؤسسة سوناطراك بالجزائر - بكوش, لطيفة; بن ساهل, وسيلة (جامعة الوادي - University of Eloued, 2014)
يحاول هذا العمل دراسة العلاقة بين بطاقة الأداء المتوازن وتقييم الأداء البيئي للمؤسسة. تطرح هذه الإشكالية نظرا لصعوبة إيجاد نموذج ملائم لتقييم الأداء يأخذ بعين الاعتبار كافة انشغالات المؤسسة الحالية، وكذلك إلى صعوبة التوفيق بين الآراء المتعارضة حول مردودية المتغيرات البيئية. إذ يعتبر البعض الالتزامات البيئية عبئا من شأنه أن يضخم تكاليف المؤسسة ويضر بسير نشاطها، بينما يعتبرها آخرون شبه استثمار حالي يحقق للمؤسسة قيمة مضافة مستقبلية وعوائد خيالية، وآلية مفيدة لتحسين كفاءة الإنتاج، صورة المؤسسة ومكانتها في السوق وتحقيق الشرعية التي تصبو المؤسسة إليها. في إطار هذا العمل تمكنا من الاستنتاج أن بطاقة الأداء المتوازن يمكن أن تكون أداة أكثر فعالية للمؤسسة إذا ما تم توسيعها لتأخذ في الاعتبار الاعتبارات البيئية. This work attempts to study the relationship between the balanced performance card and the environmental performance assessment of the institution. This problem arises because of the difficulty of finding an appropriate model for performance evaluation that takes into account all the concerns of the current institution, as well as the difficulty of reconciling conflicting views on the profitability of environmental variables. Some consider environmental commitments to be a burden that will inflate the costs of the institution and harm its business. Others consider it as a current investment that provides the organization with future added value and fictitious returns, a useful mechanism to improve the efficiency of production, the image of the institution and its position in the market. As part of this work we have been able to conclude that a balanced scorecard can be a more effective tool for the institution if it is expanded to take into consideration environmental considerations.
مقال
Keywords: بطاقة الأداء المتوازن ، الأداء البيئي; Balanced performance card, environmental performance